2019
DOI: 10.1186/s12864-019-5532-5
|View full text |Cite
|
Sign up to set email alerts
|

2C-ChIP: measuring chromatin immunoprecipitation signal from defined genomic regions with deep sequencing

Abstract: Background Understanding how transcription occurs requires the integration of genome-wide and locus-specific information gleaned from robust technologies. Chromatin immunoprecipitation (ChIP) is a staple in gene expression studies, and while genome-wide methods are available, high-throughput approaches to analyze defined regions are lacking. Results Here, we present carbon copy-ChIP (2C-ChIP), a versatile, inexpensive, and high-throughput technique to quantitatively mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…We found that depleting HOTAIRM1 slowed the rate at which cells increase confluency after RA induction (Figure 2I). Onset of this delay occurred within hours, in line with HOTAIRM1's rapid and potent induction by RA and an early role in differentiation ( [12], and results below). Cell growth was hampered until at least Day 2, and this effect was reproduced across biological replicates (Supplementary Figure S1).…”
Section: Depleting Hotairm1 Hampers Cell Proliferation During Early N...mentioning
confidence: 56%
See 2 more Smart Citations
“…We found that depleting HOTAIRM1 slowed the rate at which cells increase confluency after RA induction (Figure 2I). Onset of this delay occurred within hours, in line with HOTAIRM1's rapid and potent induction by RA and an early role in differentiation ( [12], and results below). Cell growth was hampered until at least Day 2, and this effect was reproduced across biological replicates (Supplementary Figure S1).…”
Section: Depleting Hotairm1 Hampers Cell Proliferation During Early N...mentioning
confidence: 56%
“…When determining HOTAIRM1 RNA levels, we considered its spliced and unspliced forms, as both were found in NT2-D1, with functional implications in HOXA cluster regulation [7]. As expected, both HOTAIRM1 forms were not significantly expressed before differentiation and were potently induced by RA (Figure 2E, Supplementary Table S1) [7,12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When applicable (e.g., for 2C-ChIP libraries), tracks are normalized by input DNA counts and optionally corrected for sample-specific DNA density. Density correction is based on TaqMan quantification of total DNA yield following immunoprecipitation, as well as various dilution steps that occur in the preparation of pooled libraries as detailed in Wang and Cameron et al [3].…”
Section: Normalizationmentioning
confidence: 99%
“…Ligation-Mediated Amplification (LMA) library preparation protocols [1,2] have become increasingly useful in targeted sequencing methodologies. Applications include Carbon Copy-Chromatin Immunoprecipitation (2C-ChIP) [3], used to study protein-DeoxyriboNucleic Acid (DNA) interactions at a defined set of loci, and Chromosome Conformation Capture Carbon Copy (5C) [4], for the targeted analysis of chromatin architecture. These assays generally produce single-read sequencing data and are often highly multiplexed.…”
Section: Introductionmentioning
confidence: 99%